Increased levels in vivo of mRNAs for IL-8 and macrophage inflammatory protein-1α (MIP-1α), but not of RANTES mRNA in peripheral blood mononuclear cells of patients with atopic dermatitis (AD) - Hatano, Y (Blackwell Science Inc, 1999)
Chemokines play an important role in the selective movement of leucocytes into inflammatory areas and they also activate various cells in inflamed tissues. However, it is unclear which cells are the main sources of chemokines in actual inflammatory diseases, even though both mononuclear cells and non-inflammatory resident cells are able to produce chemokines in vitro and the former cells are also the main target of chemokines. To clarify the roles of chemokines that are produced by mononuclear cells in AD, we measured levels in vivo of mRNA for IL-8 and MIP-1α, as well as the level of regulated upon activation normal T cell expressed and secreted (RANTES) mRNA in freshly isolated peripheral blood mononuclear cells from patients with AD. We compared the results with those from psoriatic patients, and patients without AD who were suffering from other cutaneous diseases and eosinophilia. Levels of mRNAs were determined by semiquantitative reverse transcriptase-polymerase chain reactions. Levels of IL-8 and MIP-1α mRNA were elevated not only in atopic patients but also in non-atopic patients with inflammatory skin disease associated with eosinophilia, compared with levels in psoriatic patients and healthy controls. Levels of RANTES mRNA were similar in atopic patients but they were lower in the other two groups of patients when compared with levels in healthy controls. In atopic patients, the levels of both IL-8 and MIP-1α mRNAs but not of RANTES mRNA decreased with improvements in symptom scores after therapy. These findings suggest that mononuclear cells are not only the target of chemokines but might also play an important role in the pathogenesis of AD by producing IL-8 and MIP-1α.